2014
DOI: 10.15560/10.3.650
|View full text |Cite
|
Sign up to set email alerts
|

Calomys tener (Winge, 1887) (Rodentia: Cricetidae: Sigmodontinae): Filling gaps

Abstract: Calomys tener is a widely distributed species in Brazil. Herein we report the second record of C. tener in state of Rio Grande do Sul about 80 km northwestwards from the previous southernmost known limit in Brazil. A fragment of 890 bp of Cytochrome b gene (cyt b) from MCN -MAM 42 was sequenced and the sequence identity was first investigated by using BLAST (Basic Local Alignment Tool) (Altschul et al. 1990) in order to observe its similarity levels with other sequences deposited in the GenBank. We also perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The record of the rodent Calomys tener, for instance, is new for restinga habitats in Southeastern Brazil and also represents the first occurrence of the species in the littoral of Rio de Janeiro state. This species inhabits dry and open vegetation formations in central Brazil, and its marginal records in Southeastern Brazil did not include littoral zones or coastal localities east to the Serra do Mar (Almeida et al 2007;Bonvicino et al 2010), despite its widespread occurrence in the coast of Southern Brazil (Quintela et al 2014). The most coastal localities reported for this species in Southeastern Brazil were the municipalities of Santa Tereza, in Espírito Santo state, and Itapetininga, in São Paulo state (Bonvicino et al 2010).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The record of the rodent Calomys tener, for instance, is new for restinga habitats in Southeastern Brazil and also represents the first occurrence of the species in the littoral of Rio de Janeiro state. This species inhabits dry and open vegetation formations in central Brazil, and its marginal records in Southeastern Brazil did not include littoral zones or coastal localities east to the Serra do Mar (Almeida et al 2007;Bonvicino et al 2010), despite its widespread occurrence in the coast of Southern Brazil (Quintela et al 2014). The most coastal localities reported for this species in Southeastern Brazil were the municipalities of Santa Tereza, in Espírito Santo state, and Itapetininga, in São Paulo state (Bonvicino et al 2010).…”
Section: Discussionmentioning
confidence: 96%
“…Mammalian diversity in the Brazilian Atlantic forest is relatively high in comparison to those found in other biomes in Brazil, being distributed throughout a wide range of physiognomies that includes dense and humid forests to coastal sandy plains covered by shrublands and dry forests (Paglia et al 2012). These coastal sandy plains, commonly termed restingas, are discontinuously distributed along the Brazilian littoral near river mouths or zones of past marine transgressions, harboring varied biotas, lagoons and vegetation types, some of which adapted to dry or arid conditions (Cerqueira 2000, Esteves 2011.…”
Section: Introductionmentioning
confidence: 94%
“…2 show the same global topology with the following relationships: (C. tener (C. laucha and the big clade including all the large-bodied species of Calomys)). Quintela et al (2014) recorded for the first time the sympatry between C. tener and C. laucha and warned that the distribution limits in the Rio Grande do Sul state in Brazil should be investigated. Considering the two clades found for C. laucha by González-Ittig et al (2014), it is highly probable that what Quintela et al (2014) found corresponds to our clade B.…”
Section: Discussionmentioning
confidence: 99%
“…Quintela et al (2014) recorded for the first time the sympatry between C. tener and C. laucha and warned that the distribution limits in the Rio Grande do Sul state in Brazil should be investigated. Considering the two clades found for C. laucha by González-Ittig et al (2014), it is highly probable that what Quintela et al (2014) found corresponds to our clade B. Thus, there is no evidence of sympatry with C. laucha sensu stricto (or clade A) (see a discussion on the geographic distribution of the species in Teta et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation